Rehabilitation in digital environments – biophysiologically motivated gamification - Wojciechowski, Adam; Korjonen-Kuusipuro, Kristiina (Human Technology, 2022)
Nowadays, the process of cognitive or motor rehabilitation is mostly implemented in a traditional form. Paper-pencil cognitive exercises or physical exercises with instruments still dominate over digital environments. However, they require constant supervision by professionals, whose availability is relatively decreasing in an ageing society. Lack of supervision, in turn, results in a loss of motivation to exercise or, at the very least, ineffective, sometimes incorrect, exercise. In addition, traditional rehabilitation mechanisms are often repetitive and tedious. Sometimes a lack of supervision or routine results in a failure to adapt the challenges to the user’s current needs. Digital environments and modern technology have much to offer in this regard. One aspect is gamification mechanisms, which work well in video games and allow players to be engaged for hours in challenges of modulated difficulty. Another aspect is the rapidly developing biosensors and tracking systems that allow the user’s activity and biophysiological parameters to be monitored in real time. However, the combination of the benefits of technology and gamification stimulus mechanisms must be done in strict accordance with the user’s capabilities in order to make the challenges constructive rather than destructive for the user’s body and mental conditions. Ongoing monitoring of effort and mental workload and their synchronization with fatigue in the digital environment, supported by motivational gamification mechanisms, form the foundation of the correct and controlled exercises and rehabilitation.